2007
DOI: 10.1111/j.1467-8276.2007.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Asset Pricing in Created Markets

Abstract: We investigate the applicability of the present-value asset pricing model to fishing quota markets by applying instrumental variable panel data estimation techniques to 15 years of market transactions from New Zealand's individual transferable quota (ITQ) market. In addition to the influence of current fishing rents, we explore the effect of market interest rates, risk, and expected changes in future rents on quota asset prices. The results indicate that quota asset prices are positively related to declines in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Arnason (1993), Newell, Sanchirico et al (2005), Wilen (2005), Newell, Papps et al (2007), and Agar et al (2014)). For example, Newell, Sanchirico and Kerr (2005) found that the value of fishing quota in New Zealand increased over time for fisheries with greater degrees of freedom to change their fishing operations post-ITQ implementation (such as inshore and shellfish fisheries relative to specialized deep-water fisheries).…”
Section: Literature Review On Itq Fisheriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Arnason (1993), Newell, Sanchirico et al (2005), Wilen (2005), Newell, Papps et al (2007), and Agar et al (2014)). For example, Newell, Sanchirico and Kerr (2005) found that the value of fishing quota in New Zealand increased over time for fisheries with greater degrees of freedom to change their fishing operations post-ITQ implementation (such as inshore and shellfish fisheries relative to specialized deep-water fisheries).…”
Section: Literature Review On Itq Fisheriesmentioning
confidence: 99%
“…Most of these performance assessments have been done on developed world fisheries (Jardine and Sanchirico 2012), which is a reflection of where most of the early adopters of rights-based systems are found (e.g., Iceland, New Zealand, Canada), and the locations where the data are rich enough to measure impacts (see, e.g., Grafton, Squires et al 2000, Shotton 2001, Newell, Sanchirico and Kerr (2005, Newell, Papps and Sanchirico (2007), Chu (2009), andMRAG (2009)). …”
Section: Introductionmentioning
confidence: 99%
“…This bias is a reflection of both where most of the early adopters of rights based systems are found (e.g., Iceland, New Zealand, Canada), as well as the locations where the data are rich enough to measure impacts (see, e.g., Grafton, Squires and Fox (2000), Shotton (2001), Newell, Sanchirico and Kerr (2005), Newell, Papps and Sanchirico (2007), Chu (2009), and MRAG (2009)). With the number of programs and their diversity increasing, a universal set of indicators was developed to permit comparisons across socioeconomic and biological performance of various fisheries management programs (Brinson and Thunberg 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In these types of management programs initial recipients receive quota shares, a percentage of an overall total allowable catch (TAC) in the fishery, which are translated into annual IFQ allocations (fishable pounds). Although numerous researchers have documented the success of these management regimes at increasing economic efficiency, profitability, and product quality, improving safety, managing the harvest within the TAC, and overall working conditions in the fisheries (Arnason 2005, Brinson and Thunberg 2013, Campbell et al 2000, Costello et al 2008, Dupont 2000, Grafton 1995, Grimm et al 2012, Hilborn et al 2005, Hughes and Woodley 2007, Newell et al 2005a, others have shown that these types of management programs can have adverse impacts on some stakeholders and coastal communities due to consolidation and associated employment losses, changes in processing needs, and shifts in regional distribution of fishing privileges (Carothers 2008, Carothers et al 2010, Copes and Charles 2004, McCay 2004, Olson 2011.…”
Section: Introductionmentioning
confidence: 99%